The The Effect of 9 Weeks of Weight Training on Cardiovascular Endurance in Sedentary Adults - Yeliz Doğru (Ilmu Inovasi Nusantara, 2026)
Sedentary lifestyles among adults represent a major risk factor for cardiovascular and metabolic diseases. Physical inactivity is associated with decreased cardiovascular endurance, elevated resting heart rate, increased blood pressure, and higher body fat percentage. Therefore, effective and structured interventions are needed to improve physiological health in this population. This study aimed to examine the effects of a 9-week resistance training program on cardiovascular endurance and selected physiological parameters in sedentary adults. This study employed an experimental design involving 30 sedentary participants, divided into an exercise group (EG, n=10) and a control group (CG, n=20). The exercise group participated in a structured resistance-training program three times per week for approximately 60 minutes per session, at an intensity of 60–75% of one-repetition maximum (1RM). Pre- and post-intervention assessments included the Cooper 12-minute run test, estimated VO₂max, resting heart rate, heart rate recovery, systolic and diastolic blood pressure, and body fat percentage. Data were analyzed using paired-sample and independent-sample t-tests with a significance level of p < 0.05. The findings revealed significant improvements in the exercise group across all measured variables. Cooper test distance and estimated VO₂max increased significantly, while resting heart rate decreased and heart rate recovery improved. Additionally, systolic and diastolic blood pressure, as well as body fat percentage, showed significant reductions. In contrast, no significant changes were observed in the control group. These findings suggest that resistance training is an effective strategy for enhancing cardiovascular health and reducing metabolic risk factors in sedentary adults. This program can be recommended as a preventive and promotive health intervention in broader public health contexts